The Legal-Political Urgency of Coal Industry Downstreaming for Democratic and Just National Development - Gilang Abi Zaifa; Maria Yohana; Al Fath (Recht Studiosum Law Review, 2023)
In please fifth Pancasila and the 1945 Constitution emphasize that the principle of social justice mandates the responsibility of the government in developing welfare. After the issuance of Law NO. 3 of 2020, the mineral and coal (minerba) sector plays an important role in national economic growth. However, in practice, it is felt that the government lacks a supervisory function, resulting in a recentralization of authority, both from the aspect of licensing and supervision. Coal industry supervision mechanisms must be further regulated to ensure that the downstream coal industry is not controlled by a handful of people. The formulation of the problem in this journal is what is the mechanism for downstreaming the coal industry as a development of national law? And what is the juridical basis for the delegation of authority for the downstream coal industry in achieving national legal prosperity? This research uses normative juridical method through literature study. Normatively, the legal politics of natural resource management in Indonesia has been determined in the 1945 Constitution, specifically in Article 33 paragraph (2) and paragraph (3). In terms of planning, as well as coordination of intensity implementation supervision has not been carried out optimally, so that it has not supported the realization of sustainable and environmentally sound mining through law enforcement efforts. The recommendation from this study is that policies still need to be synchronized with the provisions of related laws and regulations so that they can become an effective, efficient and comprehensive legal basis in mining operations so as to create legal certainty and provide protection for the community.